New Product Development Process for Parts Business : From New Product Idea to Market Launch - Pietilä, Henri Matti Olavi (My University, 2024)
Varaosamyynti on tärkeä liiketoiminnan osa-alue teknologiayrityksille. Varaosat turvaavat laitteen käyttövarmuutta ja niillä voidaan päivittää uusia ominaisuuksia vanhoihin laitteisiin. Hinnan ja toimitusaikojen lisäksi tuoteinnovaatiot ovat tärkeitä kilpailutekijöitä teknologiateollisuudessa. Teknologiajohtajuuden kannalta on tärkeää, että yritys jatkuvasti kehittää tuotteittaan, ja sen lisäksi tuo markkinoille uusia innovaatioita. Uusien tuotteiden kehittämiseen viittaa englanninkielinen termi New Product Development, joka käsittää tuotteen kehittämisen tuoteideasta markkinajulkaisuun. Uusien tuotteiden kehittämisessä avaintekijät ovat selkeä tuotekehitysprosessi, dynaaminen tuotekehitystiimi, sekä asiakastarpeiden ymmärtäminen. Tämä tutkielma on tapaustutkimus, jossa kohdeorganisaationa on Konecranes Port Servicen varaosayksikkö. Tutkimuksen empiirisessä osiossa käytetään sekä laadullista että määrällistä dataa. Kohdeorganisaatio myy satamanosturien varaosia ja kehittää jatkuvasti tuoteportfolioon uusia varaosatuotteitta ja -paketteja. Kohdeorganisaation käyttöön on esitelty yleinen Stage-Gate tuotekehitys prosessi tätä varten. Tutkielman tavoitteena on selvittää, miten nykyistä prosessia voisi kehittää entistä sopivammaksi varaosaliiketoimintaan ja täsmentää vastuualueet sekä työtehtävät prosessin eri vaiheiden sisällä. Kehitysideat kerätään laadullisella tutkimusmenetelmällä haastattelemalla tuotekehityksen parissa työskenteleviä henkilöitä kohdeorganisaatiosta. Lisäksi selvitetään määrällisen datan avulla aiempien tuotekehitysprojektien läpimenoaikoja sekä prosessin pullonkaulavaihe. Tutkimuksen perusteella aiempien tuotekehitysprojektien läpimenoaika on ollut noin vuosi, vaihdellen projektin suuruudesta. Prosessin pullonkaulaksi löydettiin tekninen kehitysvaihe, joka keskimäärin kesti 192 päivää. Tutkielman jatkotutkimusideana on selvittää, miten tätä vaihetta voidaan nopeuttaa. Nykyiseen prosessiin saatiin useita kehitysideoita haastattelujen perusteella ja esitelty prosessi vastuualueineen esitellään työn lopussa.

Spare part sales is an important business for engineering-driven companies. Spare parts ensure the equipment operation security and old new features can be updated to machines by spare part packages. In addition to price and delivery times, product innovations are important competitive factors in the technology industry. From the point of view of technological leadership, it is important that the company constantly develops its products, and in addition brings new innovations to the market. New product development refers to the development of new products starting from market opportunity identification until the new product is launched to the market including the post launch-review. The factors in successful new product development are well-defined process, dynamic cross-functional team as well as understanding of customer needs. This thesis is an empirical case study research where the case organisation is a spare part organisation of Konecranes Port Service. Data is collected by mixed method meaning that both quantitative and qualitative data are used in the empirical part of the thesis. The case organisation works in spare part sales for port cranes, and constantly develops new spare part products and packages into their product portfolio. A general Stage-Gate new product development process has been introduced for the use of the case organisation. The aim of the thesis is to find out how the current process could be developed to be even more suitable for the spare part business, and to specify the areas of responsibility and tasks within the different stages of the process. Development ideas are collected using a qualitative research method by interviewing employees from the case organisation. In addition, the quantitative data is used to find out the lead times of previous new product development projects, as well as bottleneck from the previously used process, are clarified. Based on the research results, the lead time of previous new product development projects has been about a year, varying with the size of the project. The bottleneck was found to be the develop-stage which on average took 192 days. Based on the results an idea for future research is to find out how this process stage could be accelerated. Several development ideas for the current process were obtained based on the interviews, and the recommended process with areas of responsibility will be presented in the last chapter of the thesis paper.
Keywords: product development; spare parts; innovations; new products; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management